Developing the leaders around you - Maxwell, John C. (Nashville, Tennessee. Thomas Nelson Publishers., 1995)
Supremely practical, this handbook is crammed with strategies that help you effectively transform your dreams into reality by building up your people. Emphasizing that your organization can't grow until its members grow, Dr. Maxwell encourages you to identify and train potential leaders. You'll learn how to foster productive team spirit, how to make difficult decisions, what to look for in promising leaders, ways to nurture, encourage, and equip people, how to handle confrontation, and much more
Keywords: Leadership